Staff Planning at the National Library of the Netherlands - Langbroek, Dick (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
The Koninklijke Bibliotheek in the Netherlands has developed a Strategic Staff Planning Programme to deal with the challenges of an ageing workforce, succession issues for management and specialised positions, and short-term budget cuts in combination with expected long-term staff shortages. This article describes the reasons for the Programme, steps taken to develop it, and preliminary results. The programme includes a Trainee Programme, a Management Trainee Programme, Individual Career Counselling and a Career Service Centre.